E-Learning Integration: Transforming Islamic Education Through Enhanced Learning Experiences - Dahmayanti, Siti; Nurmila, Nina (Jurnal Inovasi Pendidikan Agama Islam (JIPAI), 2024)
Applying e-learning in the rapid development of technology is an alternative in using learning methods to be more optimal. The purpose of this research is to find out the application of e-learning in the improvement of learning experience in Islamic Religious Education subject. The method used in this research is using literature analysis, where data is collected and then analyzed descriptively to identify the use of e-learning in Islamic Religious Education learning. The results showed that integrating e-learning can improve the quality and effectiveness of classroom learning because students can experience a good learning experience, using e-learning can also provide easy access to various teaching materials. There are some obstacles in the application of e-learning in Islamic Religious Education learning, namely limited Internet access and devices, lack of knowledge and technology skills of teachers and students. The implication of this study is the need for support and training in the application of e-learning to improve and develop the learning experience of Islamic religious education. In addition, this finding can be a valuable reference for teachers and educational institutions to develop appropriate learning strategies for Islamic education by using technology in the form of e-learning.